Nodal segments and zygotic embryos in culture media for the in vitro propagation of tamarind - Ferreira, Antonio Flávio Arruda; da Silva, Marcela Sant'anna Cordeiro [UNESP]; Monteiro, Laís Naiara Honorato [UNESP]; Faria, Glaucia Amorim [UNESP]; Boliani, Aparecida Conceição [UNESP]; Rodrigues, Maria Gabriela Fontanetti [UNESP]; Pereira, Flávia Dionísio (Lepidus Tecnologia, 2019)
There has been a lack of research on the propagation methods of tamarind, hindering the availability and supply of its products. Considering the nutraceutical potential of tamarind and the long-time required to initiate production, this study aimed to evaluate the establishment of nodal segments and the germination of in vitro zygotic embryos of tamarind plants in culture media, salt concentrations, and activated charcoal, aiming at the establishment of an in vitro propagation protocol. For this purpose, MS and WPM media with 25, 50, 75 and 100% salt concentrations were used both with and without activated charcoal (2 g L-1) for the inoculation of nodal segments and zygotic embryos of tamarind. The experiment was conducted in a completely randomized experimental design, in a 2 x 4 x 2 factorial scheme (culture media x salt concentrations x activated charcoal) with 20 replications. It was observed that the in vitro establishment of tamarind nodal segments is viable when using the MS medium with 75% of salts plus 2 g L-1 of activated charcoal and that for the germination of zygotic embryos there was no influence of the treatments. It was also observed that in order to increase the length of the formed plantlets, the MS and WPM media can be employed with 75% of salts.
Keywords: Conservation; Explants; Micropropagation Tamarindus indica L; Plant tissue culture